1998
DOI: 10.4269/ajtmh.1998.59.763
|View full text |Cite
|
Sign up to set email alerts
|

Serologic and molecular diagnosis of Colorado tick fever viral infections.

Abstract: Abstract. Molecular and serologic methods usable for the biological diagnosis of Coltivirus infection are reported. We designed a multiplex reverse transcription-polymerase chain reaction system that allowed the simultaneous and specific amplification of three genomic segments from as little as 0.01 plaque-forming units. Another system in the S2 viral segment permitted the differential diagnosis of American and European viral isolates. We also discuss some improvements of previous ELISAs, and the results obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 22 publications
(28 reference statements)
0
13
0
Order By: Relevance
“…Primers designed from the sequences of segments 9-12 of the Florio strain (Attoui et al, 1997(Attoui et al, , 1998 of CTF virus permitted PCR amplification of these segments from the R-1575, 69V28 and S6-14-03 viruses. The amplified sequences had the same lengths as those of the Florio strain and exhibited high degrees of nucleic acid and deduced protein identities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Primers designed from the sequences of segments 9-12 of the Florio strain (Attoui et al, 1997(Attoui et al, , 1998 of CTF virus permitted PCR amplification of these segments from the R-1575, 69V28 and S6-14-03 viruses. The amplified sequences had the same lengths as those of the Florio strain and exhibited high degrees of nucleic acid and deduced protein identities.…”
Section: Discussionmentioning
confidence: 99%
“…The extracted viral dsRNAs from CTF strains R-1575 and 69V28, Eyach, AR578 and S6-14-03 viruses were resuspended in diethylpyrocarbonate-treated water. Reverse transcription was carried out as previously described in the presence of random hexanucleotides and the MMuLV Superscript CEIC reverse transcriptase (Attoui et al, 1998). PCR primers were designed from the sequences genomic segments 9-12 of the Florio strain (N-7180) of CTF virus with the help of the Oligo software program (National Biosciences).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Infection by this virus has been diagnosed by a variety of serological procedures including complement fixation, indirect immunofluoresence, IgM capture enzyme-linked immunosorbent assays (ELISAs), and plaque reduction neutralisation (Attoui et al 1998). Reverse transcription PCR has been used to detect viral RNA in acute samples of blood collected within five days of illness (Lambert et al 2007).…”
Section: Viral Diseases Colorado Tick Fevermentioning
confidence: 99%
“…This protein was highly reactive to human sera infected with CTFV and to a mouse hyper-immune ascitic fluid to CTFV. The ELISA test based on this protein (Mohd Jaafar et al, 2003) was validated using a panel of human sera, some of which were earlier found positive for CTFV antibodies by complement fixation, detection of IgG and IgM and virus neutralisation (Calisher et al, 1985;Attoui et al, 1998). Hence, it was logical to choose the homologous protein of EYAV (VP6) as a target for selectively detecting antibodies to EYAV.…”
Section: Choice Of the Antigenic Substrate For Antibody Detectionmentioning
confidence: 99%